Prognostic factors in post-prostatectomy salvage radiotherapy setting with and without hormonotherapy: An individual patient data analysis of randomized trials from ICECaP database - Pommier, Pascal; Xie, Wanling; Ravi, Praful; Carrie, Christian; Dignam, James J.; Feng, Felix; Sargos, Paul; Sommer, Silke Gillessen; Spratt, Daniel E.; Tombal, Bertrand; Van Poppel, Hendrik; Sweeney, Christopher (Radiotherapy and oncology, 2024)
•By using a composite score of pathology grading (Gleason Score), PSA at start of salvage radiation and margin status data, physicians can provide patients with more refined information on the risk of a second relapse after receiving radiation to the prostate bed after a prostatectomy for a rising or persistent PSA, both with and without hormonal therapy. Early salvage radiotherapy (SRT) is the standard of care for biochemical recurrence post-prostatectomy but outcomes are heterogeneous. To develop a risk scoring system based on relevant standard-of-care clinico-pathological prognostic factors for patients treated with SRT with and without hormonal therapy (HT). The Intermediate Clinical Endpoints in Cancer of the Prostate (ICECaP) database included three randomized trials (Individual patients’ data from 1647 subjects) assessing SRT (GETUG-AFU-16; NRG/RTOG-9601, and a subset of EORTC-22911). Outcomes were clinical progression (CP). metastasis free-survival (MFS) and overall survival (OS). Clinico-pathological factors, including pathological Gleason Score (GS), PSA at SRT start, margin status, persistent PSA post-RP and time from RP to SRT were evaluated by multivariable models stratified by type of treatment. On multivariable analysis PSA ≥ 0.5 ng/mL at SRT start, GS ≥ 8 and negative margin status were the three strongest prognostic factors. Three prognostic groups defined by number of these risk features (high risk: 2 or 3; intermediate risk: 1 and low risk: 0) were strongly associated with OS, MFS and CP outcomes with SRT alone or with HT. This prognostic group definition was also relevant for patients with persistent PSA post RP and for patients treated < 1 year from RP to SRT and with and without HT. A risk score for patients receiving SRT with or without HT, using three standard-of-care clinico-pathological risk factors provides refined prognostic information for individual patient counselling. By using a composite score of pathology grading (Gleason Score), PSA at start of salvage radiation and margin status data, physicians can provide patients with more refined information on the risk of a second relapse after receiving radiation to the prostate bed after a prostatectomy for a rising or persistent PSA, both with and without hormonal therapy.